KESESUAIAN EKOSISTEM TERUMBU KARANG UNTUK KEGIATAN WISATA SELAM DI NUSA LEMBONGAN, BALI - Ayu Pratiwi, Made; Ernawati, Ni Made; Wijayanti, Ni Putu Putri (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 15 No 1 (2021), 2021)
Nusa Lembongan islands, Bali have a potential of coral reef diversity. Coral reefs have both ecological and high economic potential so that they are widely used. The economic benefits of coral reefs make these ecosystems very vulnerable to pressure from human activities. One of these human activities is the use of coral reefs in diving tourism activities. This research aimed to determine suitability and carrying capacity of coral reef ecosystem on Nusa Lembongan Island so that it can be recommended to manage coral reef ecosystem strategies to support the use of diving tourism. This study was conducted on six dive sites as observation points Observations on coral reef ecosystems were carried out using the intercept transect (LIT) method, and reef fish observation was carried out using the fish visual census method. Water quality sampling will be done in situ. Diving suitability was carried out by estimating the tourist suitability index (IKW) of six parameters, namely the brightness of the waters, coral community cover, coral life form, reef fish species, coral reef depth and current. The tourism suitability index value for the diving tourism category obtained was 74.07% (Jack Mangrove); 57.41% (Crystal Bay); and 61.11% (Manta Bay). The value for each observation point is included in the appropriate category of 50% -75%. It can be interpreted, that all observation points which are dive sites in Nusa Lembongan have supported diving tourism activities. Keywords: Tourism Suitability Index; Diving; Nusa lembongan.